Recuperação de trajetória de ponta de caneta em assinaturas offline com referencial online - Cavalcante Neto, Luiz Miranda (2017)
The handwritten signature is a form of personal identification widely accepted, both socially and legally, used for centuries to authenticate documents such as bank checks, letters, contracts and any type of service that requires proof of authorship. When signing, an individual inserts a large amount of information to transform the movement of his hand into an identifying element. Writing speed, trajectory traversed, pen inclination, applied pressure, all these data are articulated (in the form of latent variables) to result in a static figure in the signed document. This dissertation investigates the problem of trajectory extraction of the pen that generates this signature from the resulting static image. For this, the work was divided in three main steps that are: (i) compute the skeleton of the offline signature; (ii) extract its characteristics using a concept addressed in this work called UCSS, and, with the help of previously recorded online signatures, (iii) estimate the path that the pen traveled over the skeleton. In each of these steps, a review of relevant work on the themes was done prior to begin implementation. Three experiments were carried out during this work, the first one was done with the objective of comparing the results obtained with the developed algorithm and the results obtained in a reference work, the other two were realized during the production of an article destined to the publication attached to this job.